2019
DOI: 10.1111/ncn3.12309
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of repeated botulinum toxin type A injections in trigeminal neuralgia

Abstract: Background Trigeminal neuralgia is a chronic severely disabling facial pain syndrome, which significantly affects the quality of life of patients. Drugs are effective in controlling pain, but surgery is offered in drug‐refractory cases, which may not be feasible due to lack of availability of neurosurgeons or due to unfavorable risk‐benefit ratio or patient preference. Botulinum neurotoxin is an effective alternative in patients who are drug refractory and not willing for surgery. Objectives To study the safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…There was a significant improvement in VAS in the BTX-A group versus the placebo group, while VAS scores did not differ significantly between the BTX-A groups (Taheri et al, 2020) revealed that after single and continuous injections of BTX-A, the severity of pain in patients was significantly reduced, the efficiency of pain relief was 100% in both cases, and there was no significant difference in the mean duration of pain relief. No significant adverse effects were seen in either case, suggesting that repeated injections of BTX-A are safe and effective (Gorimanipalli et al, 2019). In addition, some cases have reported that BTX-A is equally effective in trigeminal neuralgia caused by multiple sclerosis, suggesting that BTX-A can also treat atypical trigeminal neuralgia (Calejo et al, 2019).…”
Section: Trigeminal Neuralgiamentioning
confidence: 76%
See 1 more Smart Citation
“…There was a significant improvement in VAS in the BTX-A group versus the placebo group, while VAS scores did not differ significantly between the BTX-A groups (Taheri et al, 2020) revealed that after single and continuous injections of BTX-A, the severity of pain in patients was significantly reduced, the efficiency of pain relief was 100% in both cases, and there was no significant difference in the mean duration of pain relief. No significant adverse effects were seen in either case, suggesting that repeated injections of BTX-A are safe and effective (Gorimanipalli et al, 2019). In addition, some cases have reported that BTX-A is equally effective in trigeminal neuralgia caused by multiple sclerosis, suggesting that BTX-A can also treat atypical trigeminal neuralgia (Calejo et al, 2019).…”
Section: Trigeminal Neuralgiamentioning
confidence: 76%
“…The efficacy of BTX-A combined with 0.2% local anaesthetic ropivacaine hydrochloride injection (BTX group) with ropivacaine hydrochloride injection alone (LA group) for the treatment of pelvic floor myofascial syndrome and chronic pelvic pain showing that neither group exhibited any significant differences on day 60. However, the two groups showed an overall improvement in pain, meaning that intramuscular injection with ropivacaine hydrochloride alone was justified (Gorimanipalli et al, 2019;Levesque et al, 2021). The randomized clinical trials of BTX-A for myofascial pain has also been elaborated (Table 1).…”
Section: Myofascial Painmentioning
confidence: 99%
“…The most common reasons for exclusion were insufficient data, followed by incorrect indication and inappropriate study design. Among the included studies, 45 were noncontrolled observational studies 2,7‐41 (Table I) and 29 were randomized controlled trials 3,4,9,23,40,42‐64 (Table II). One study reported on multiple trials, including an observational study and a randomized controlled trial 9 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 24 therapies assessed. Carbamazepine was the most common intervention examined across studies, with 19 observational studies 5,6,[20][21][22][27][28][29][30][31]33,35,[65][66][67][68][69][70][71] and 9 randomized controlled trials, 23,44,[47][48][49]58,59,62,63 followed by botulinum toxin A with 11 observational studies 8,[12][13][14][15][16][17][18][19]41,72 32 oxcarbazepine, 7,36,44 pregabalin, 39 valproic acid, 38 gabapentin, 6,21,73 lamotrigine 21,60,62,64 ), local anesthetics (lidocaine, 37,53,57,61,67 tocainide 48 ), selective serotonin receptor agonists (sumatriptan…”
Section: General Study Interventions and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation